(3GdMbs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3YHO Gddg Hf eMeO YHGO s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdUeO GdPi dGjbHd GdTHjg CeG HYO aEf GdfXjQ ef MjK GdfYJ hGdhUa bO jhLO ai LejY GdehLhOGJ cdgG s
(3BNQgG (B:s
(3aEf GdeUdi jfGLi QHg , adjbHV GdYfGf hjbhe GdESHGZ GdhVhA GdWghQ , hefGLGI GdQMef , hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B7 - (3U(B10s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs